IMPLEMENTATION OF REGIONAL SPATIAL PLANNING (RTRW) EFFORTS TO REALIZE SUSTAINABLE CITY DEVELOPMENT (ANALYSIS STUDY OF MEDAN CITY'S REGIONAL SPATIAL PLANNING (RTRW) - Arwynta Nasution; Abdiyanto; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2024)
This research explains howImplementation of Regional Spatial Planning (RTRW) Efforts to Realize Sustainable City Development (Analysis study of Medan City's Regional Spatial Planning (RTRW).This research uses a qualitative descriptive method, a type of literature study which aims to describe the results of the researchers' findings on several journal articles found.This literature review was carried out with the awareness that knowledge will continue to develop along with changes and progress over time. The purpose of the literature review is for the benefit of the research project itself. Research resultSpatial planning activities are interrelated, namely spatial planning, space utilization, and control of space utilization which are outlined in spatial planning products in the form of RTRW in a hierarchical manner from central to regional. Regional spatial planning is one of the mandatory affairs of regional governments in the regional autonomy regime, which is reflected in Article 13 and Article 14 of the Regional Government Law. Development is not only related to programs and activities, but also attention to spatial aspects towards sustainable development and regional economic growth. In reality, implementation in the field has not been able to fully provide optimal results regarding regional independence in general. Geographical conditions as well as diverse characteristics and unequal availability of resources are fundamental factors so that these efforts do not run with the same quality.